Funding innovation and bank systemic risk: Evidence from Wealth Management Products - Aftab, Saad; Mallick, Sushanta; Matousek, Roman (Journal of Financial Stability, 2026)
Wealth Management Products (WMPs) have become a major source of bank funding over the past decade. Using a unique WMP transactions dataset from China covering 99,893 transactions during 2010-2020, this study examines whether greater reliance on WMPs as a type of funding innovation increases bank systemic risk. We find that higher WMP dependence significantly elevates systemic risk, with the effects concentrated among smaller banks. Exploiting the 2018 Asset Management Regulation as an exogenous shock, we establish causality using a difference-in-differences approach. Our channel analysis shows that maturity mismatch amplifies WMP-related systemic risk, while higher WMP yields further increase fragility through funding cost pressures. Overall, these results call for a regulatory approach that moves beyond aggregate balance-sheet metrics and instead targets funding composition, maturity structure, and pricing behaviour-dimensions in which WMPs materially increase systemic vulnerability.